Analisis Pengembangan Smart City berdasarkan Dimensi Teknologi, Sumber Daya Manusia, dan Insitutional di Kota Padang Panjang - Anggi Syahadat Harahap; Pepi Zulvia (KLIK: Kajian Ilmiah Informatika dan Komputer, 2023)
The smart city concept and all applications that have been created by the Padang Panjang City Government need to be studied and developed further. The purpose of this research was conducted in order to describe the extent of implementing smart cities and recommendations for improvement for the government in terms of technological, human resource, and institutional dimensions. The research method was carried out in an exploratory qualitative manner. Data obtained from interviews with authorized officials and in-depth observations regarding several applications that have been published. The dimensions explored consist of 3 parts, namely technology, human resources and institutions. In the technological dimension, the research results obtained are seen from the software sub-dimension and the hardware sub- dimension, where the results of the two sub dimensions need to be improved and optimized again, because most of the existing applications in Padang Panjang City are still not integrated with each database. In terms of the human resource dimension, there are still many Regional Apparatus Organizations that have not consistently updated data due to a shortage of experts in this field and the need for outreach to the public regarding the use of the application. Meanwhile, in the institutional dimension, looking at the regulations or policies implemented, it is good with the smart city master plan. From the results of these three dimensions, it was found that there is a need to develop a smart city in Padang Panjang City. An important focus of development, namely collaboration between government and society, needs to be improved and improved. So that the realization of a smart city that supports people who are smart, educated, have morals and improve the quality of life of residents in the city of Padang Panjang.